Association between gynecological disorders and insomnia and depression trajectories: a longitudinal study of middle-aged women - Zhong, Huiyong; Zeng, Fuling (Frontiers in Psychiatry, 2025)
BackgroundInsomnia and depression often receive inadequate attention regarding their association with common menopausal gynecological disorders (GDs), and there is a lack of longitudinal epidemiological evidence. Furthermore, the specific disorders that exhibit the strongest correlation with depression, as well as the potential mediating role of insomnia, remain poorly understood.MethodsUsing data from the Study of Women’s Health Across the Nation (SWAN) spanning 1996 to 2008, this study analyzed a sample of 2217 racially diverse premenopausal women (aged 42 to 53 at baseline). Longitudinal trajectory analysis, employing latent class mixture models (LCMM), was used to identify optimal patterns for insomnia and depression. Logistic regression explored associations between pelvic pain, pelvic prolapse or relaxation, abnormal bleeding, and insomnia/depression trajectories. A causal mediation model investigated whether insomnia mediated the link between gynecological disorders and depression.ResultsThe analysis included 2217 participants for insomnia trajectories and 1767 for depression trajectories. Insomnia and depression showed similar patterns, with a single high and low trajectory and minimal fluctuations. Logistic regression revealed a significant positive correlation between pelvic pain, abnormal bleeding, number of GDs, and an increased risk of high insomnia and depression trajectories. Insomnia trajectories mediated 23.6%, 14.3%, and 11.9% of the association between pelvic pain, abnormal bleeding, and number of GDs, respectively, with depression trajectories.ConclusionsThis study found the significant associations between pelvic pain, abnormal bleeding, and comorbidity with an elevated risk of insomnia and depression during the menopausal transition.